(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the QT dispersion for coronary artery disease in cardiac stress test by transesophageal atrial pacing in patients with coronary heart disease. Study Design: Randomized control trial study. Place and Duration of Study: This study was conducted at Bolan Medical College Hospital Quetta from 1st July 2012 to 30th Jun 2013. Materials and Methods: Sample size of 58 cases were included in the study through non-probability, purposive sampling. The informed consent and demographic details were noted and the patients underwent through tocolytic trial either by i/v ritodrine or transdermal nitroglycerine patch. The data was analyzed by using SPSS-10 software. Both groups were compared by using chi-square test taking p-value<0.05 as significant. Results: In Nitroglycerine group, there were 20 (69%) cases in which effectiveness of drug was achieved while in Ritodrine group, there were 23 (79.3%) cases in which effectiveness of drug was achieved. The difference between both study groups was insignificant (p-value = 0.368). There were 3 patients who complaint about headache, out of which there were 2 (6.9%) cases belonged to nitroglycerin group while 1 (3.4%) cases belonged to ritodrine group. There were 13 patients who complaint about tachycardia, 1 patient who complaint about breathlessness and 2 patients in which hypotension was observed. All these cases belonged to ritodrine group. Conclusion: The efficacy of both drugs almost equal, the side effects of ritodrine were more severe and there were more cases who complaint about side effects. Hence nitroglycerine patch is effective drug with less side effects, as a result is more appropriate to manage patients with preterm labour.